IPTEKS NILAI WAKTU UANG DAN IMPLIKASI PENCATATAN AKUNTANSI - Budiarso, Novi Swandari (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2019)
Most of general public and firms know about money and its value but do not have better understanding how the money creates its own value relates to interest rate. Another side, most of firms still not realize that the time value of money has an impact on accounting recording and its reporting in financial statements, such as statement of financial position (balance sheet), income statement, and statement of cash flows.